Language and Visual Representation in Physics: Enhancing Understanding Through Multimedia - Nasution, Eni Sumanti; Nasution, Fauziah; Harahap, Tinur Rahmawati; Tambunan, Elissa Evawani (International Journal of Educational Research Excellence (IJERE), 2025)
The incorporation of multimedia resources in physics education has become a crucial approach for improving student understanding by combining verbal and visual components. This investigation utilizes a mixed-methods design to assess the impact of multimedia tools on student participation and comprehension in physics courses. Quantitative information was gathered through assessments before and after the intervention, while qualitative data was obtained from student interviews and in-class observations. The study involved creating tailored multimedia materials, which were subsequently integrated into lessons. Quantitative data underwent statistical analysis, including paired t-tests, while qualitative findings were examined using thematic analysis. The results revealed a substantial increase in student engagement from 45% without multimedia to 85% with its use. Additionally, the post-test mean score (79.3 ± 8.81) exceeded the pre-test average (58.5 ± 12.65), suggesting enhanced understanding and uniformity among students. Qualitative outcomes highlighted multimedia's contribution to clarifying intricate concepts, improving communication abilities, and promoting collaborative learning. The research concludes that the strategic integration of multimedia tools within cooperative frameworks can establish a vibrant, interactive learning environment, considerably enhancing students' conceptual grasp and preparing them for future academic and career challenges.